Pattern of utilization of antenatal care services in a rural area of Tamil Nadu: a community based cross-sectional study - Sugumaran, Arun; Subramanian, Rajkumar; Tharumaraj, Muthukumar; Vaithiyalingam, Saravanan (International Journal Of Community Medicine And Public Health, 2019)
Background: In India, 17 per cent or nearly 50,000 of 2.89 lakh women died as result of complication due to pregnancy in 2013. In past decade, many studies have revealed low utilization of health services by different segments of society for varying reasons. This study was conducted to assess the utilization pattern of ANC services by the pregnant women in a rural area. The objectives of the study were to assess the pattern of utilization of ANC services by pregnant and recently delivered women; to study the association between socio-demographic factors and utilization pattern among recently delivered women. Methods: A community based cross-sectional study conducted at the rural health training centre in Kancheepuram district, Tamil Nadu among pregnant women and recently delivered women using pre-designed and pre-tested questionnaire. The entire registered pregnant mothers were included for the study and survey was done through house to house visit and the analysis was done using SPSS 21. Results: Out of 170 study participants, majority 132 (77.6%) of them had their antenatal check-up at primary health centre, 138 (81.2%) have received the IFA tablets and 139 (81.8%) had early antenatal registration. And most of the study participants 108 (63.5%) did not utilize anganwadi for health education and supplementary nutrition. Number of IFA tablets consumption by mothers was significantly associated with literacy and socio-economic status of the mother with p value of 0.03 and 0.002 respectively. Conclusions: Our study results showed that better ANC services utilization pattern in our study area except anganwadi utilization.